Birth experience in newborn infants is associated with changes in nociceptive sensitivity - Kasser, Severin; Magerl, Walter (Scientific reports, 2019)
Vaginal birth prepares the fetus for postnatal life. It confers respiratory, cardiovascular and homeostatic advantages to the newborn infant compared with elective cesarean section, and is reported to provide neonatal analgesia. We hypothesize that infants born by vaginal delivery will show lower noxious-evoked brain activity a few hours after birth compared to those born by elective cesarean section. In the first few hours of neonatal life, we record electrophysiological measures of noxious-evoked brain activity following the application of a mildly noxious experimental stimulus in 41 infants born by either vaginal delivery or by elective cesarean section. We demonstrate that noxious-evoked brain activity is related to the mode of delivery and significantly lower in infants born by vaginal delivery compared with those born by elective cesarean section. Furthermore, we found that the magnitude of noxious-evoked brain activity is inversely correlated with fetal copeptin production, a surrogate marker of vasopressin, and dependent on the experience of birth-related distress. This suggests that nociceptive sensitivity in the first few hours of postnatal life is influenced by birth experience and endogenous hormonal production.